Biomarkers of drug resistance in ovarian cancer – an update. (3rd June 2019) - Davidson, Ben
ABSTRACT: Introduction : Ovarian cancer, consisting predominantly of ovarian carcinoma, is the most lethal gynecologic malignancy. Diagnosis at the advanced stage, particularly in high-grade serous carcinoma which is the most common and clinically aggressive histotype, is a major factor negatively affecting survival, while tumor heterogeneity and chemoresistance often preclude complete elimination of tumor cells even following radical surgery and combination chemotherapy. Recently, inhibition of angiogenesis and inhibition of poly (ADP-ribose) polymerase (PARP) have shown benefit in the treatment of this cancer. Areas covered : Extensive research has identified molecules associated with resistance to chemotherapy and implicated several biomarkers affecting response to antiangiogenic therapy and PARP inhibition. This review discusses recent data in this field. The presented data, gathered in a PubMed search focusing on the years 2016–2018, focus on regulators of the cell cycle and mitosis, cancer stem cell-related molecules, the immune response, receptor tyrosine kinases and related signaling pathways, BRCA and other DNA repair molecules, microRNAs, and other cancer-associated molecules. Expert opinion : Future research is likely to focus on histotype-specific analyses of clinical specimens and patient-generated cultures applying cutting-edge molecular technology, in the aim of identifying major regulators of chemotherapy response.